2020
DOI: 10.1103/physreve.101.042130
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of hysteresis in absorption of hydrogen by a Pd-Au alloy

Abstract: Hydrogen absorption by Pd exhibits hysteresis loops (provided the temperature is not too high) and represents one of the classical examples of first-order phase transitions in metals. Experiments indicate that addition of even a small amount of Au is able to suppress hysteresis. From this perspective, we analyze the energetics of hydrogen in a Pd-Au alloy by using extensive density-functional-theory (DFT) calculations. The dependence of the hydrogen binding energy on the number (n) of Au atoms forming an adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
3
4
0
Order By: Relevance
“…5b-c), the SRO parameter is negative, indicating that H is more likely to occupy sites next to Pd than next to Au. This confirms what has been observed both with Mössbauer spectroscopy [60] and firstprinciples calculations [24], namely that it is energetically unfavorable for hydrogen to occupy the sites closest to a Au atom. For next-nearest Pd/Au-H/vacancy neighbors (Fig.…”
Section: Hydrogen Loading Of Fixed Pd-au Lattice: Random and Para-equ...supporting
confidence: 90%
See 3 more Smart Citations
“…5b-c), the SRO parameter is negative, indicating that H is more likely to occupy sites next to Pd than next to Au. This confirms what has been observed both with Mössbauer spectroscopy [60] and firstprinciples calculations [24], namely that it is energetically unfavorable for hydrogen to occupy the sites closest to a Au atom. For next-nearest Pd/Au-H/vacancy neighbors (Fig.…”
Section: Hydrogen Loading Of Fixed Pd-au Lattice: Random and Para-equ...supporting
confidence: 90%
“…3b). As has been previously reported [24] and can be expected from the ECIs (Fig. 2), occupation of hydrogen at such sites is energetically particularly favorable, and renders this long-range ordered phase particularly stable.…”
Section: E Hydrogen Loading In Full Equilibriumsupporting
confidence: 82%
See 2 more Smart Citations
“…Mechanistically, this can be understood as the Au atoms, which occupy Pd lattice sites, slightly expanding the Pd host. Thereby, they reduce the strain-induced energy barrier created upon hydrogen sorption, and thus hysteresis. , To this end, Wadell et al have shown that alloying Pd with 25 at % Au reduces sensor uncertainty to below 5% across the 1–1000 mbar H 2 pressure range, which is on par with the corresponding performance target by the US DoE. Similarly, alloying with metals with smaller atomic radius than Pd, e.g., Cu and Ni, also suppresses hysteresis at ca.…”
Section: Rational Design Of Nanostructured Pd-based Hydrogen Sensorsmentioning
confidence: 99%